Measurement of blood flow in the human Achilles tendon in vivo - Keitaro Kubo; Tomonobu Ishigaki; Toshihiro Ikebukuro (Japanese Society of Physical Fitness and Sports Medicine, 2017)
The purpose of this study was to apply a high-power laser blood flowmeter and laser oxygenation monitor to investigate 1) changes during a single isometric contraction and 2) changes after repeated contractions in blood flow (BF), blood volume (THb), and oxygen saturation (StO2) in the human Achilles tendon in vivo. Subjects (n = 17) performed isometric contractions at 10%, 30%, and 50% of the maximum voluntary contraction (MVC) for 1 min. Subjects (n = 10) also performed five sets of 50 repetitions at 70% of MVC for 1 second (s), and remained relaxed for 20 min. During isometric contractions at all torque levels, BF decreased significantly from resting level regardless of torque level, whereas THb during contractions tended to decrease with increases in torque level. After repeated contractions, BF, THb, and StO2 were higher during the recovery period than resting level. These results show that 1) BF in the tendon was already interrupted during 10% of MVC to the same degree as that during 50% of MVC, whereas THb during contractions slightly decreased with increases in the torque level and 2) blood circulation (BF, THb, and StO2) within the tendon was facilitated further after repeated contractions.